Tinjauan Kritis Sosial: Terorisme di Indonesia - Tukina, Tukina (Humaniora, 2011)
In the last few months, terrorism has become in interesting talks and debates. Unfortunately, terrorism study is minimum. Terrorism is an act or behavior that criticizes the existing civilization, especially west civilization. Terrorism topic could be studied from multidiscipline science, from social science, political, economical, and also religious. Terrorism study will be able to give contribution in solving terrorism problems accordingly. Terrorism problems involved complicated and wide dimension. In order to solve terrorism problems, it needs to be understood the way terrorism begins. Terrorism behavior is an act that must be its trigger. In order to solve terrorism overall, the trigger must be defined so the solution will be clear. Justice creates a world order, and is an important tool in reducing terrorist acts in addition to other efforts should also be made. This should be done immediately, because terrorism itself is due to many factors, and must also have interest in it.